Factors Influencing Mothers in Providing Vitamin A Capsules to Toddlers - Latifa Khoiriah; Kismi Asih Adethia; Eka Falentina Tarigan; Rohmiati Tumangger (Health Dynamics, 2025)
Background: Vitamin A is an essential micronutrient required by the body. According to the World Health Organization (WHO) in 2014, approximately 250 million preschool-aged children experience vitamin A deficiency. This study aimed to determine the factors influencing mothers in providing vitamin A capsules to toddlers. Methods: This research employed an analytical observational study with a cross-sectional design. The study was conducted at Sidomulyo Public Health Center, Banyuasin Regency, in May 2023. The sample consisted of 51 mothers with toddlers. Results: The cross-tabulation results between attitude and the provision of vitamin A capsules showed that the majority of mothers who provided vitamin A capsules had a positive attitude, totaling 23 respondents (45.1%). The chi-square test results indicated a p-value of 0.003 (<0.05). The cross-tabulation results between behavior and the provision of vitamin A capsules showed that the majority of mothers who provided vitamin A capsules to toddlers had good behavior, totaling 26 respondents (51.0%). The chi-square test results indicated a p-value of 0.001 (<0.05). Conclusion: There was a significant association between maternal attitude and behavior and the provision of vitamin A capsules to toddlers. It is recommended that the head of Sidomulyo Public Health Center pay greater attention to factors influencing mothers in providing vitamin A capsules to toddlers by using the findings of this study as a reference.